Counting Functions to Generate The Primes in the RSA Algorithm and Diffie-Hellman Key Exchange - AL-Maamori, Faez Ali; Rashid, Mazin Saied (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The Rivestâ€“Shamirâ€“Adleman (RSA) and the Diffie-Hellman (DH) key exchange are famous methods for encryption. These methods  depended on selecting the primes p and q in order  to be secure enough . This paper shows that the named methods used the primes which are found by some arithmetical function .In the other sense, no need to think about getting primes p and q and how they are secure enough, since the arithmetical function enable to build the primes in such complicated way to be secure. Moreover, this article   gives  new construction  of the  RSA  algorithm and DH key  exchange using theprimes p,qfrom areal number x.